The operation Performance Evaluation and Maintenance of Suka Damai Irrigation System in Sei Bamban District Serdang Bedagai Regency - Annisa Kasanra Lubis; Sumono Sumono; Lukman Adlin Lubis (Universitas Sumatera Utara, 2016)
Suka Damai irrigation area is one of half-technical irrigation area with an area of 300 ha that is located in Sei Bamban District Serdang Bedagai regency. This study was aimed to evaluate the performance of operation and maintenance of Suka Damai irrigation system. This research was conducted in April 2015 in Sei Bamban District Serdang Bedagai regency. Some of the indicators used to determine the performance of the irrigation system were : physical and functional condition of infrastructure of the irrigation network, the adequacy of water, the level of accuracy of water supply, the management of government institution, human resources, the farmer institution performance, and the availability of funding. The results showed that : physical and functional condition of infrastructure irrigation network was bad with the value of 2, the adequacy of water was sufficient with the value of 3, the level of accuracy of water supply, the management of government institution, human resources, and the farmer institution performance was very good with the value of 4, and then the availability of funding was very bad with the value of 1. In general, the performance of operation and maintenance of the Suka Damai irrigation system was categorized well with a value of 2.96. Keywords: Evaluation of the performance, operation and maintenance, irrigation system, Suka Damai